Eustress as a Driver of Islamic Educational Organizational Performance: A Systematic Literature Review: Eustres sebagai Pendorong Kinerja Organisasi Pendidikan Islam: Tinjauan Pustaka Sistematis - Nurul Ulfa Ramadhani; Sarah Fadilah Azzahra; Gunawan Abdirohman; Salfen Hasri; Sohiron Sohiron (Academia Open, 2027)
General Background Islamic educational institutions in Indonesia face growing organizational pressure amid curriculum reform and broader educational change. Specific Background Existing research predominantly treats occupational stress as harmful, although positive organizational psychology recognizes eustress as a potentially constructive response to manageable demands. Knowledge Gap Research on Islamic education remains fragmented across burnout, psychological capital, stress, and performance, with no systematic synthesis positioning eustress as a positive organizational resource in this context. Aims Using a PRISMA-guided systematic literature review of peer-reviewed studies published from 2015 to 2024 and sourced from Scopus, Web of Science, and Google Scholar, this study identifies conceptual foundations, performance mechanisms, moderating factors, and a practical management model grounded in Islamic educational values. Results Three interconnected mechanisms were identified: strengthened intrinsic motivation, stronger self-efficacy, and development of an adaptive organizational climate aligned with amanah and istiqamah. Transformational-Islamic leadership and colleague support emerged as key moderators of eustress appraisal. Novelty The study proposes the School-Based Eustress Management Model, integrating psychological capital development, value-based meaning, and protective leadership and administration as a contextually grounded conceptual framework. Implications The model offers a basis for teacher development and institutional policy, but it is intended for future empirical testing rather than as a validated intervention. Highlights: Intrinsic motivation, self-efficacy, plus adaptive climate emerged as three central mechanisms. Transformational religious leadership together with colleague support moderated appraisal of constructive pressure. MMEBS integrates psychological capital, value-based meaning, plus protective administration but remains empirically unvalidated. Keywords: Eustress, Organizational Performance, Islamic Education, Work Motivation, Stress Management.